Analisis Pengaruh Konsentrasi Gula Terhadap Karakteristik Fisik Dan Kimia Manisan Buah Tomat - Muhpidah Muhpidah; Amran Laga; Maura Rahmah Tahta Naula; Gemala Hardinasinta; Arfina Sukmawati Arifin; Khaeril Anwar Junaedi (Jurnal Agritechno, 2025)
Tomatoes represent a promising raw material for conversion into candied fruit due to their texture and flesh, which possess a distinctive sour taste well-suited for this application. This study seeks to evaluate the impact of varying sugar concentrations during the cooking process on the physical and chemical properties of candied tomatoes. Variations in sugar concentration influence the water content, texture, and color of the resultant candied tomatoes. The lowest water content, 4.6%, was achieved with a 60% sugar concentration. Texture analysis revealed that the highest hardness value was also obtained with a 60% sugar concentration. Additionally, the candied tomato samples exhibited the highest level of redness in the final product when a 60% sugar concentration was employed. These findings suggest that sugar concentration differentially affects the tested attributes, with a 60% concentration yielding the highest values in texture and color analysis, while resulting in the lowest water content compared to the 50% and 40% sugar concentrations.